The complete chloroplast genome sequence of economical standard tea plant, Camellia sinensis L. cultivar Sangmok, in Korea. Issue 3 (2nd July 2020) - Lee, Dong-Jun; Kim, Chang-Kug; Lee, Tae-Ho; Lee, So-Jin; Moon, Doo-Gyung; Kwon, Yong-Hee; Cho, Jeong-Yong
Abstract: The complete chloroplast genome sequence of Camellia sinensis L. cultivar Sangmok was determined using high-throughput sequencing technology. We sequenced Sangmok chloroplast genome and performed comparative with 21 published other Camellia and species from different genus for phylogenetic analysis. Chloroplast genome was 153, 044 bp in length, containing a pair of 24, 627 bp inverted repeat (IR) regions, which were separated by small and large single-copy regions (SSC and LSC) of 19, 155 and 64, 665 bp, respectively. The chloroplast genome contained 97 genes (63 protein-coding genes, 29 tRNA genes, and 5 rRNA genes). The overall GC content of the chloroplast genome was 37.2%. The phylogenetic analysis among species in number of the genus Camellia provided that C. sinensis L. cultivar Sangmok is closely related to KJ806277 Camellia pubicosta .